Expenditure and Trend in State Aid for Regional Development in the European Union in the Years 2004–2010 - Rutkiewicz, Krzysztof (Wydawnictwo Uniwersytetu Rzeszowskiego, 2012)
This paper discusses the issue of state aid for regional development granted in EU in 2004–2010. It provides a general overview of state aid levels and the most important objectives supported by Member States. The article consists of 5 parts including: 1) explanatory of state aid concept in the EU competition policy; 2) image of the structure and total amount of aid using empirical data in absolute and relative terms; 3) analysis of the trend in aid for horizontal and sectoral objectives; 4) insight into the structure and average amount of aid granted by Member States for regional development; 5) investigation of a number of decisions on regional development aid relating to EU countries and issued by Commission.

Artykuł przybliża problematykę pomocy publicznej udzielanej na rozwój regionalny UE w latach 2004–2010. Zawiera on omówienie ogólnego poziomu pomocy oraz przegląd najważniejszych celów finansowego wsparcia publicznego w państwach UE. Opracowanie składa się z 5 części obejmujących: 1) przedstawienie koncepcji pomocy publicznej w świetle polityki konkurencji UE; 2) charakterystykę struktury i wartości pomocy opartą na danych empirycznych w ujęciu bezwzględnym oraz jako % PKB UE-27; 3) analizę trendu pomocy ukierunkowanej na cele horyzontalne i sektorowe; 4) omówienie struktury i średniej wartości pomocy na rozwój regionalny w państwach UE; 5) badanie liczby decyzji wydanych przez Komisję, dotyczących pomocy regionalnej w poszczególnych krajach.